Artrópodos associados à diferentes cultivares de nogueira-pecã Carya illinoinensis (Wangenh.) K. Koch na região central do estado do Rio Grande do Sul, Brasil - Silva, Bruna Casanova (2021)
The presente study aimed to qualitatively and quantitatively assess the diversity of insects pests and natural enemies associated with different pecan cultivars. The experiment was evaluated monthly and conducted in a completely randomized (DIC), in a three factor scheme consisting of five treatment: T1: Cultivar Barton; T2: Cultivar Melhorada; T3: Cultivar Importada; T4: Cultivar Shawnee; T5: Cultivar Imperial. Collections of pecan cups were performed during the seven-month period with the aid of and entomological net. The abundance richness and diversity between cultivars were evaluated. In total 4989 individuals were collected referring to six orders. The greatest diversity was found in T4. The orders Diptera, Hemiptera and Coleoptera were the most abundant in the respective treatments evaluated. Monellia Caryella was the main insect pest, its spatio-temporal distribution is abundantly concentrated during the period of the walnut harvest. However, in the summer season, care must be take with insect monitoring, as in this period there is a higher frequency of individuals in pecan orchards.